2021
DOI: 10.3389/fpsyg.2021.673586
|View full text |Cite
|
Sign up to set email alerts
|

An Ontology-Based Framework for Psychological Monitoring in Education During the COVID-19 Pandemic

Abstract: BackgroundEspecially in the current crisis of the COVID-19 pandemic and the lockdown it entailed, technology became crucial. Machines need to be able to interpret and represent human behavior, to improve human interaction with technology. This holds for all domains but even more so for the domain of student behavior in relation to education and psychological well-being.MethodsThis work presents the theoretical framework of a psychologically driven computing ontology, CCOnto, describing situation-based human be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 93 publications
(109 reference statements)
0
9
0
Order By: Relevance
“…, 2015). Ontologies about education can be categorized into four main categories: curriculum modeling and management, describing learning domains, describing e-learning services, and describing learning data, which are used to develop lesson plans, assess learning effectiveness, exchange learning profiles, predict learning styles (Bolock et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, 2015). Ontologies about education can be categorized into four main categories: curriculum modeling and management, describing learning domains, describing e-learning services, and describing learning data, which are used to develop lesson plans, assess learning effectiveness, exchange learning profiles, predict learning styles (Bolock et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is found that KO involves 16 research methods, the most common of which are model development and validation (e.g. Bolock et al. , 2021; Strassner and Diab, 2016; Wang et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dramatic and sudden changes in working and learning environments accompanied the pandemic, with many workplaces and classrooms becoming fully or partially remote during lockdowns, with consequently reduced quantities of social encounters and potentially reduced access to social support. In one study, an ontology-driven representation of individual psychological states and traits was used to characterise learner well-being during the pandemic [27]. An online psychological survey used a mix of measures including big five personality traits, depression screening, state and trait anxiety measures, feelings towards the pandemic, worries about mental and physical health, sentiments about social distancing, perceived difficulties identifying and representing emotions, changes in behavioural patterns, and general emotions.…”
Section: Health Behaviours and Health Behaviour Changementioning
confidence: 99%